Japan's carnival war : mass culture on the home front, 1937-1945 - Uchiyama, Benjamin, 1979- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2020)
"This book is about the evolution of mass culture into what I term "carnival war" in Japan, reorienting our perspectives on daily life between 1937 and 1945. Although the Asia-Pacific War created the opportunity for the state to expand its control over society, it also fractured Japanese people's sense of identity, which spilled out through a cultural framework which, this book will argue, is best understood as carnival war. Carnival war encompassed both "official" cultural practices shining in the spotlight and "unofficial" cultural practices lurking in the shadows. It requires thinking not only about the activities of official purveyors of entertainment like Kinoshita Circus, but also the "ghetto" circus, the half-man, half-dog circus freaks who echoed, mocked, and inverted the pristine, official national culture the wartime state was trying to build. Second, a study of carnival war examines the unevenness of state attempts to mobilize society for war; the dynamic, improvisational dimension to total war mobilization"--
The reporter -- The munitions worker -- The soldier -- The movie star -- The youth aviator -- Gendering carnival war -- Global echoes of carnival war -- The circus freak next to the policeman.
Revision of author's thesis (doctoral)--University of Southern California, 2013, titled Carnival war : a cultural history of wartime Japan, 1937-1945.
First published 2019.
Includes bibliographical references (pages 263-276) and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Popular culture -- Political aspects -- Japan -- History -- 20th century; War and society -- Japan -- History -- 20th century; Political culture -- Japan -- 20th century; Japan -- Civilization -- 1926-1945.